Adding value to lignocellulosic byproducts by using acetate and p-coumaric acid as substrate in a microbial fuel cell - Mancilio, Lucca Bonjy Kikuti; Ribeiro, Guilherme Augusto; de Almeida, Erica Janaina Rodrigues [UNESP]; de Siqueira, Guilherme Marcelino Viana; Rocha, Rafael Silva; Guazzaroni, María-Eugenia; De Andrade, Adalgisa Rodrigues [UNESP]; Reginatto, Valeria (Elsevier, 2021)
Acetate and p-coumaric acid, which inhibit fermentation, are important byproducts from the sugarcane biomass pretreatment and hydrolysis steps. At the same time, organic and phenolic acids are valuable substrates to produce bioelectricity in Microbial Fuel Cells (MFCs). Here, we operated an MFC with a synthetic non-fermentable fraction of sugarcane biomass hydrolysates; we employed acetate spiked with p-coumaric acid as substrates. At maximum activity of the bacterial community, the potential and power density of the MFC fed with acetate alone reached 0.47 V and 478 mW m−2, respectively; upon addition of 0.1 mM p-coumaric acid, these values decreased to 0.34 V and 398 mW m−2, respectively. p-Coumaric acid at 0.1 mM was efficiently metabolized (79 %) in the MFC by a minimalist, but robust bacterial community composed mainly of Pseudomonas spp. and Pseudochrobactrum spp. Our work suggests that p-coumaric acid can be applied to generate energy, adding value to a non-fermentable fraction obtained in the sugarcane biorefinery.
Keywords: Bioelectricity; Biomass; Microbial fuel cell; Pseudochrobactrum; Pseudomonas